Indicadores de qualidade da educação básica sob o olhar da pesquisa científica: Prova Brasil e IDEB - Andrade, Alenis Cleusa de (Universidade do Vale do Rio dos Sinos, 2015)
This study aims to investigate how information gathered by large scale evaluation are interpreted through scientific research. It highlights scientific researches related to different areas of knowledge regarding post-graduation Estrito Sensu, involving thesis and dissertations, for five years from 2007 to 2011. These researches raise questions related to Primary Education, Prova Brasil and Ideb quality indicators. Goals aim to analyze: how the possible ways of interpretation of primary school quality indicators, through different areas of knowledge, represent contributions to knowledge advance concerning large scale evaluation and to the advance of educational management and, how from concepts which surpass different social areas of social and applied sciences, administration and human sciences subarea, education subarea what contributions they bring to the understanding of these advances. Theoretical foundation is inspired on Bourdieu's (2003), scientific field theory, to identify special provisions of knowledge areas. The investigation scope of educational policies bases itself on Ogza(2000). Supported by Barroso's studies (2004), (2005) it interprets multi regulation processes which influences the teaching's management system. The research's methodology is bibliographical. The scientific production appreciation is based on content analyses. The study's results say that not all interpretation ways of information regarding large scale evaluation represent advances to knowledge not only of evaluation policies, but also educational management processes. Many knowledge areas now consider the indicators as structuring elements of its methodological board, only for specific researches determining a new way of understanding the investigations therefore, spreading indirectly large scale evaluation mechanisms throughout the academic niche. There is dominance on theoretical cases investigations related to each area of knowledge, education and administration, understanding evaluation's policies. The interpretation of the educational management context is also, linked to the thoretical determinations of each area of knowledge showing the stresses present in these processes. However, on two sciences spheres there are evidences of movement regarding educational management besides contributions coming from both knowledge areas, educational and administration, to improve performance.
Keywords: Avaliação em larga escala; Política educacional; Campo científico; Escola básica; Large scale evaluation; Educational policy; Scientific area; Primary school; ACCNPQ::Ciências Humanas::Educação